Revisioning Official Islam in Indonesia: The Role of Women Ulama Congress in Reproducing Female Authority in Islamic Law - Mun'im, Zainul; Nasrudin, Muhamad; Suaidi, Suaidi; Hasanudin, Hasanudin (Universitas Islam Negeri Jakarta, 2024)
Until now, the religious views of the Indonesian Government, known as official Islam, tend to be masculine and patriarchal in determining laws. The masculinity of official Islam can easily be found in some regulations in Indonesia. The establishment of the Indonesian Congress of Women Islamic Scholars (Kongres Ulama Perempuan Indonesia, KUPI) has introduced a new perspective on gender amid the dominance of official Islamic masculinity. This article focuses on the role and position of KUPI amid the dominance of official Islamic masculinity in Indonesia. Through content analysis and Charles Peirce's theory of knowledge construction, the author found that KUPI has successfully become a center for reproducing female authority in Islamic law. This is achieved by reinterpreting several government rules and policies that tend to be masculine and disadvantageous to women. The success of KUPI as a center for the reproduction of the authority of women Islamic scholars plays a role in revising official Islam. KUPI accomplishes this by offering a new paradigm that embodies the values of justice and gender equality. Abstrak: Pandangan-pandangan keagamaan Pemerintah Indonesia yang dikenal dengan istilah official Islam selama ini masih cenderung maskulin dan patriarki dalam menetapkan hukum. Maskulinitas official Islam dapat dengan mudah ditemukan dalam sebagian aturan di Indonesia. Penyelenggaraan Kongres Ulama Perempuan Indonesia (KUPI) memunculkan perspektif baru terkait gender di tengah dominannya maskulinitas Official Islam tersebut. Artikel ini menganalis peran dan posisi KUPI di tengah dominannya maskulinitas Official Islam di Indonesia. Melalui pendekatan content analysis dan teori konstruksi pengetahuan Charles Peirce, penulis berargumen bahwa KUPI telah berhasil menjadi pusat reproduksi otoritas ulama perempuan di Indonesia. Hal ini dicapai dengan melakukan penafsiran ulang terhadap beberapa aturan dan kebijakan pemerintah yang cenderung maskulin dan merugikan perempuan. Keberhasilan KUPI menjadi pusat reproduksi otoritas ulama perempuan ini berperan dalam merevisi Official Islam tersebut. Hal ini dilakukan oleh KUPI dengan menawarkan paradigma baru yang lebih mengandung nilai-nilai keadilan dan keseteraan gender.